Engineered Bacteriophage Therapeutics: Rationale, Challenges and Future - Łobocka, Małgorzata (BioDrugs, 2021)
The current problems with increasing bacterial resistance to antibacterial therapies, resulting in a growing frequency of incurable bacterial infections, necessitates the acceleration of studies on antibacterials of a new generation that could offer an alternative to antibiotics or support their action. Bacteriophages (phages) can kill antibiotic-sensitive as well as antibiotic-resistant bacteria, and thus are a major subject of such studies. Their efficacy in curing bacterial infections has been demonstrated in in vivo experiments and in the clinic. Unlike antibiotics, phages have a narrow range of specificity, which makes them safe for commensal microbiota. However, targeting even only the most clinically relevant strains of pathogenic bacteria requires large collections of well characterized phages, whose specificity would cover all such strains. The environment is a rich source of diverse phages, but due to their complex relationships with bacteria and safety concerns, only some naturally occurring phages can be considered for therapeutic applications. Still, their number and diversity make a detailed characterization of all potentially promising phages virtually impossible. Moreover, no single phage combines all the features required of an ideal therapeutic agent. Additionally, the rapid acquisition of phage resistance by bacteria may make phages already approved for therapy ineffective and turn the search for environmental phages of better efficacy and new specificity into an endless race. An alternative strategy for acquiring phages with desired properties in a short time with minimal cost regarding their acquisition, characterization, and approval for therapy could be based on targeted genome modifications of phage isolates with known properties. The first example demonstrating the potential of this strategy in curing bacterial diseases resistant to traditional therapy is the recent successful treatment of a progressing disseminated Mycobacterium abscessus infection in a teenage patient with the use of an engineered phage. In this review, we briefly present current methods of phage genetic engineering, highlighting their advantages and disadvantages, and provide examples of genetically engineered phages with a modified host range, improved safety or antibacterial activity, and proven therapeutic efficacy. We also summarize novel uses of engineered phages not only for killing pathogenic bacteria, but also for in situ modification of human microbiota to attenuate symptoms of certain bacterial diseases and metabolic, immune, or mental disorders.